Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1177/07067437221140383
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic Testing for Major Depression: A Qualitative Study of the Perceptions of People with Lived Experience and Professional Stakeholders

Abstract: Objectives With increasing evidence for the clinical utility of pharmacogenomic (PGx) testing for depression, there is a growing need to consider issues related to the clinical implementation of this testing. The perspectives of key stakeholders (both people with lived experience [PWLE] and providers) are critical, but not frequently explored. The purpose of this study was to understand how PWLE and healthcare providers/policy experts (P/HCPs) perceive PGx testing for depression, to inform the consideration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…There is evidence that community-based approaches are effective in engaging communities historically under-represented for enhanced participation in pharmacogenetics studies. [34][35][36][37][38] Such efforts have been successfully used to reduce the power imbalance between investigators and participants as well as improve study participation.…”
Section: Global Collaboration and Diversified Leadership To Enhance D...mentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that community-based approaches are effective in engaging communities historically under-represented for enhanced participation in pharmacogenetics studies. [34][35][36][37][38] Such efforts have been successfully used to reduce the power imbalance between investigators and participants as well as improve study participation.…”
Section: Global Collaboration and Diversified Leadership To Enhance D...mentioning
confidence: 99%
“…Community leaders would be empowered to play more prominent roles in the investigation (e.g., providing input for study design decisions, contributing as authors). There is evidence that community‐based approaches are effective in engaging communities historically under‐represented for enhanced participation in pharmacogenetics studies 34‐38 . Such efforts have been successfully used to reduce the power imbalance between investigators and participants as well as improve study participation.…”
Section: How We Can Ensure That Cyp2d6 Pharmacogenetics Benefits Allmentioning
confidence: 99%
“…Our participation in this research project on mental health has led to creativity, inclusivity, and a cooperative ethos within our team, with plenty of space for kindness and laughter along the way. We were integrated into components of the project that we chose: thematically coding a rapid review, developing questions and advising on engagement processes for focus groups [ 16 ], shaping an economic model [ 15 ]. We were offered and accepted invitations for contributing to abstracts, manuscripts, presentations, and the funder’s biannual progress reports.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…Our lived experience of depression has been a foundation of the project meetings, treated with respect and Riches et al Research Involvement and Engagement (2023) 9:24 validated by the researchers. We were included in all aspects of the research, clearly seen in our involvement with co-creating the computer simulation model for our project [15], assisting in a literature review, and co-contributing to the creation of interview guides and questionnaires for potential study participants [16]. Since patient partners shaped these study methods, we directly influenced project-wide results.…”
Section: Draw On Lived Experiencementioning
confidence: 99%
“… 24 Additionally, it was found that PGx application in psychiatry is further challenged by the high cost of testing and the lack of cost effectiveness studies as reported by a previous research to assess concerns of HCPs regarding PGx testing in depression. 22 , 25 …”
Section: Introductionmentioning
confidence: 99%